Structure and surface analysis of ibuprofen-organotin conjugate: Potential anti-cancer drug candidacy of the compound is proven by in-vitro DNA binding and cytotoxicity studies. (1st December 2020) - Iqbal Farooqi, Shahid; Arshad, Nasima; Perveen, Fouzia; Ali Channar, Pervaiz; Saeed, Aamer; Javed, Aneela; Hökelek, Tuncer; Flörke, Ulrich
Graphical abstract: Anti-cancer drug candidacy of ibuprofen-organotin conjugate is proved by theoretical and experimental studies on structure, surface, DNA binding and cytotoxicity activity. Highlights: X-ray single crystal & Hirshfeld surface analysis of ibuprofen-organotin conjugate. Theoretical & experimental DNA binding investigations. Huh-7 cancer cell line studies for cytotoxicity activity. Good correlations between theoretical, experimental and biological findings. Abstract: An ibuprofen-organotin conjugate (TPTDI) was synthesized by reacting ibuprofen with triphenyltin hydroxide (fentin hydroxide) in dry ethanol under acidic conditions. Characterization data of the compound, obtained by spectroscopic techniques (FTIR, 1 H NMR and 13 C NMR), elemental analysis and its X-ray single crystal were found to corroborate the stoichiometry and structure of the title organotin (IV) ester. A detailed Hirshfeld surface analysis for the elucidation of possible intermolecular interactions indicated that the most important contributions to the crystal packing were from H…H (66.7%), H…C/C…H (27.9%) and H…O/O…H (5.3%) interactions. Hydrogen-bonding and van der Waals interactions were the dominant interactions in the crystal packing. TPTDI – DNA binding studies were done by DFT, molecular docking, UV–visible and fluorescence spectroscopies, cyclic voltammetry (CV) and by viscosity measurements at neutral pH (7.0) and at 37 °C. Theoretical and experimental investigations were found compatible and revealed significant reactivity of TPTDI with DNA via mixed mode of interaction. Binding parameters (ΔG, Kb and n) confirmed the reaction spontaneity and intercalation as prominent mode along with groove binding. In-vitro Huh-7 cancer cell line activity suggested TPTDI to be a potential anti-cancer drug candidate. Molecular, chemical and biological findings showed good correlations.